Effect of fuel quality on combustion evolution and particle emissions from PFI and GDI engines fueled with gasoline, ethanol and blend, with focus on 10–23 nm particles. (15th January 2022) - Catapano, Francesco; Di Iorio, Silvana; Magno, Agnese; Vaglieco, Bianca Maria
Abstract: The European Commission is planning to lower the particle cut off size down to 10 nm to consider the contribution of the sub-23 nm particles. Within the European project Sureal-23, a comprehensive study on the sub-23 nm particles was performed and novel technologies for their sampling and measurement were developed. One new proposed instrument, the Half Mini Differential Mobility Analyser (HM-DMA), was used in the present study. The investigation was carried out on a small direct/port fuel injection, spark ignition engine fueled with gasoline, ethanol and a 30 %v/v ethanol blend. Results highlighted a general reduction of the number and the size of the particles emitted by pure ethanol. The effect of the ethanol blend on sub-23 nm particle emissions was affected by the operating condition and the injection strategy. The extent of the VOF depends on the fuels as well as on the engine configuration and operating condition. Some differences were noted between the results from EEPS and HM-DMA ascribable to the different measurement principle and to the processes occurring in the dilution system. Highlights: Measure of the particles in the size range 10–23 nm. A novel instrument for sub-23 nm particle emissions was employed. Effect of sampling condition temperature on sub-23 nm particles was analyzed. Volatile organic fraction of sub-23 nm particles emitted by both PFI and GDI SI engines was evaluated. Particles emitted by gasoline, ethanol and a 30 %v/v of ethanol blend were compared.